Morphological analysis of inflecting compound words in Bangla - Dasgupta, Sajib; Khan, Naira; Sarkar, Asif Iqbal; Pavel, Dewan Shahriar Hossain; Khan, Mumit (BRAC University, 2010)
Includes bibliographical references (page 7-8).